Author’s Onomasticon of Olena Ryzhko: a Case Study of Stories for Young Adults (Linguostylistic Studies, 2021)
The study of the pedagogical heritage of Vasyl Sukhomlynsky is especially relevant today in connection with the implementation of the New Ukrainian school conception, according to which the goal of education is the comprehensive development of a man as a personality and the highest value of society. These ideas were developed, promoted, and put into practice by a talented Ukrainian pedagogue-humanist. The texts created by him provide an opportunity to reconstruct the motives, goals, and attitudes of the author. In this approach, the focus on personal factors of language creation is motivated. Therefore, the purpose of the article is to identify and analyze the lexical dominants of V.Sukhomlynsky's pedagogical discourse in his work One Hundred Tips for Teachers. The authors interpret pedagogical discourse as a special type of a text, which is complete in terms of content and structure. The study has revealed that the body of nominations in the text of "Tips" combines two subsystems: functional-descriptive, which involves the topical pedagogical vocabulary, and conceptual, reflected in pedagogical terms. However, both groups of vocabulary have one thing in common - they are used within the pedagogical discourse framework. Nominations represent thematically related lexical units of the text that form lexical-thematic groups. The lexical dominants form the core of text lexical groups, which attract other members of the lexical-thematic group. The research findings argue that the nominations related to the concepts of ‘pedagogy’ and ‘education’ dominate in the text of ‘Tips’. V.Sukhomlinsky emphasizes primarily the educational function of the teacher. In view of this, the central paradigm in his pedagogical discourse is teacher/ educator - students/pupils, and the core nomination is education/upbringing. The lexemes school, pedagogy, and lesson are the basic components of the author's neonyms, which reflect the innovative ideas of V. Sukhomlinsky: school of cordiality, school of observation, lesson of thinking, parental pedagogy. Basic lexemes pedagogy, education, training, skills, school, lesson, assessment are part of the terms of didactics and language clichés of pedagogical discourse, built mainly on models of subordinate dependence of components.
Keywords: pedagogical discourse; pedagogical terms; professionally marked vocabulary